Analisis Stabilitas Pada Teknologi Mortar Busa Dalam Perencanaan Flyover Sp.SKA Kota Pekanbaru - Ropiska Alfareza; Syawal Satibi; Muhamad Yusa (Sekolah Tinggi Teknologi Pekanbaru, 2023)
Hoarding on soft soil has been done in several ways so that a structure can be built properly, one of which is using light material as a pile on soft soil. Stability analysis will be carried out on the embankment using foam mortar at Flyover SP.SKA. Modeling is done using the finite element method in the plaxis 16 program, this study uses Mohr – Coulomb for selected embankments, while the Linier Elastic model is for light embankments. In the analysis in the oprit Flyover SP.SKA model of foam mortar heap, the Safety Faktor value (SF) is 7,795 for a 30 day waiting time , while in conventional heaps the Safety Faktor value (SF) is 3,910 a 30 day waiting time.